Quantum-chemical studies of the interaction of partially oxidized graphene-like planes with each other - Hrebelna, Y.V.; Demianenko, E.M.; Terets, M.I.; Sementsov, Y.I.; Lobanov, V.V.; Grebenyuk, A.G.; Kuts, V.S.; Zhuravskyi, S.V.; Khora, O.V.; Kartel, M.T. (Physics and Chemistry of Solid State, 2023)
Using the methods of quantum chemistry, the energy effects of the interaction of partially oxidized graphene-like planes with each other and the effect on this characteristic of the nature of the functional groups present in the oxidized graphene-like planes, as well as the dimensions of the graphene-like planes themselves, were clarified. It was established that the reaction between the hydroxyl and aldehyde groups of two interacting graphene-like planes is the most thermodynamically probable, regardless of the dimensions of the graphene-like planes. The reaction between two carboxyl groups of different graphene-like planes is the least thermodynamically probable. To create nanocomposites by interacting graphene-like planes with each other, it is necessary that the graphene-like planes contain hydroxyl and aldehyde groups.